2016
DOI: 10.1590/0104-6632.20160332s20140074
|View full text |Cite
|
Sign up to set email alerts
|

Stability Improvement of Immobilized Alkaline Phosphatase Using Chitosan Nanoparticles

Abstract: -Enzyme engineering via immobilization techniques is a suitable approach for improving enzyme function and stability and is superior to the other chemical or biological methods. In this study chitosan nanoparticles were synthesized using the Ionic Gelation method and were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). Alkaline phosphatase was successfully immobilized on the chitosan nanoparticles in optimum conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…In the FTIR spectrum of chitosan nanoparticles, a broad peak at 3436 cm −1 corresponds to the -NH and -OH stretching vibrations. The weak band at 2930 cm −1 corresponds to –CH stretching, whereas vibrational bands at 1640 cm −1 , 1560 cm −1 , and 1320 cm −1 may be attributed to the amide carbonyl stretch and -NH bend of the amine groups in the chitosan nanoparticles [32]. The band at 1099 cm −1 represents C–O bond stretching.…”
Section: Resultsmentioning
confidence: 99%
“…In the FTIR spectrum of chitosan nanoparticles, a broad peak at 3436 cm −1 corresponds to the -NH and -OH stretching vibrations. The weak band at 2930 cm −1 corresponds to –CH stretching, whereas vibrational bands at 1640 cm −1 , 1560 cm −1 , and 1320 cm −1 may be attributed to the amide carbonyl stretch and -NH bend of the amine groups in the chitosan nanoparticles [32]. The band at 1099 cm −1 represents C–O bond stretching.…”
Section: Resultsmentioning
confidence: 99%
“…The optimum temperature for immobilized enzyme was specified 45 °C, which is 5 °C higher than that of free inulinase. The increase in the structural rigidity and decrease in the flexibility of the immobilized inulinase via covalent bonding can justify the higher optimum temperature of immobilized enzyme compared with free enzyme [ [23] , [24] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A similar appearance of CNPs was also observed in previous studies. 40,41 The different surface characteristics and morphology of CNPs from CS and TPP molecules suggested that the nano-sized CNP system was formed through association between these molecules and constituted a population of spherical particles. The differences in surface characteristics of CNPs from CS and TPP molecules were significant, as smaller-sized CNPs can only be formed through cross-linking between CS and TPP molecules at a specific volume ratio as exhibited by DLS data.…”
Section: Morphology and Size Of Cnp Ga-cnp And Fga-cnpmentioning
confidence: 99%